2020
DOI: 10.1021/acs.analchem.0c03875
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Heterogeneity Imaged in a Uranium Fuel Pellet with Extreme Ultraviolet Laser Ablation and Ionization Time-of-Flight Mass Spectrometry

Abstract: We use extreme ultraviolet laser ablation and ionization time-of-flight mass spectrometry (EUV TOF) to map uranium isotopic heterogeneity at the nanoscale (≤100 nm). Using low-enriched uranium fuel pellets that were made by blending two isotopically distinct feedstocks, we show that EUV TOF can map the 235U/238U content in 100 nm-sized pixels. The two-dimensional (2D) isotope maps reveal U ratio variations in sub-microscale to ≥1 μm areas of the pellet that had not been fully exposed by microscale or bulk mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…12,13 In a recent publication, we demonstrated EUV TOF's high spatial resolution capabilities to map isotopic heterogeneity in a uranium fuel pellet. 14 More specifically, we showed that EUV TOF can map the 235 U/ 238 U isotope ratio in 100 nm sized pixels. The results revealed microscale (>100 nm) heterogeneity with domains characteristic of the two starting materials (i.e., feedstock).…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…12,13 In a recent publication, we demonstrated EUV TOF's high spatial resolution capabilities to map isotopic heterogeneity in a uranium fuel pellet. 14 More specifically, we showed that EUV TOF can map the 235 U/ 238 U isotope ratio in 100 nm sized pixels. The results revealed microscale (>100 nm) heterogeneity with domains characteristic of the two starting materials (i.e., feedstock).…”
Section: Introductionmentioning
confidence: 79%
“…The EUV TOF mass spectrometer, developed and built at CSU, has been described in detail elsewhere. [12][13][14] In brief, the table-top Ne-like Ar 8+ EUV capillary discharge laser 16 (sized 0.4 m 2 or ~3 ft 2 ) operates at a wavelength of 46.9 nm with a maximum pulse energy of ~10 µJ and duration of ~1.5 ns. 17 The EUV laser beam illuminates a free-standing zone plate (NA = 0.12) that focuses the beam onto the sample.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations